Keterlibatan dalam Kegiatan dan Kesejahteraan Subjektif Mahasiswa - Utami, Muhana S. (Faculty of Psychology, Universitas Gadjah Mada, 2009)
Subjective well being is one indicator of individualÊ¹s and society quality of life. This study aimed to examine the studentÊ¹s involvement on activity and gender as predictors of subjective well being. The participants in this study were 271 undergraduate student at Psychology Study Program of Psychological and Social Culture Science Faculty of Indonesian Islamic University (78,23 % female, and 21,77% male). Participants responded to a questionnaire consisting of involvement of student on activity. Subjective well being was measures by three scales: (1) The SWBâ€SWLS (positive affect, negative affect, and global life satisfaction); (2) The SWB â€“ SLS Scale (positive affect, negative affect, and life satisfaction at campus); and (3) The SWBâ€“PLS Scale (positive affect, negative affect, and personal life satisfaction. The parametric statistic method of t â€“ test and nonparametric method of testâ€U Mann Whitney analysis showed that the student involvement in extracurricular, profit, and various activities had higher subjective well being than the student didnâ€™t involved in any activities. Nevertheless, this study showed that there was no difference of subjective well being between female and male.